Design of a Mobile Application and Evaluation of Its Effects on Psychological Parameters of Covid-19 Inpatients: A Protocol for a Randomized Controlled Trial - Aalaei, Shokoufeh; Khoshrounejad, Farnaz; Saleh, Lahya Afshari; Amini, Mahnaz (Frontiers in Psychiatry, 2021)
Background: Panic of the disease and the associated concerns can lower the quality of life and physical performance. As long as the COVID-19 pandemic is ever on the rise, the psychological pandemic of the disease is on the rise, too. The high prevalence of COVID-19 has further increased physicians’ work pressure. Patients’ needs are not met adequately by physicians. It seems essential to use aids to monitor patients’ needs and serve them properly. Thus, in the present research, suggestions are made on how to evaluate patients’ physical and psychological conditions during the treatment via a mobile application. Methods and analysis: The present research is a randomized, two parallel-group, controlled trial. One-hundred-twelve inpatients diagnosed with the coronavirus will be assigned randomly to the control and intervention groups. In the intervention group, a mobile application will be provided to educate patients, establish two-way interactions between patients and care providers and record patients' symptoms. Those in the control group will receive the usual care. The primary outcome is the change to the depression anxiety stress scales-21 (DASS-21) score from the baseline to 2 weeks after discharge from hospital. It will be measured at the baseline, at the time of discharge, and two weeks later. Ethics and dissemination: The Ethics committee of Mashhad University of Medical Sciences’ approval date was 2020-04-19 with IR.MUMS.REC.1399.118 reference code. Thus far, participants’ recruitment has not been completed and is scheduled to end in March 2021. The results will be disseminated in a peer-reviewed journal. Trial registration: IRCT20170922036314N4 (https://www.irct.ir/trial/47383).